Effect of surface bugholes on chloride penetration of concrete coated with penetrants. Issue 5 (30th March 2022) - Hu, Liangjun; Yoshitake, Isamu; Sayama, Masayuki; Sayama, Shoichi
Abstract : Bugholes, considered an aesthetic problem, generally appear on concrete surfaces. Such surface imperfections may accelerate the ingression of liquids and chlorides. Chloride penetration is of crucial concern for reinforced concrete in a saline environment. Various surface penetrants have been widely used to protect concrete from environmental corrosion. However, most previous research on penetrants was conducted on concrete with minimal surface imperfections, such as bugholes or cracks. These surface blemishes bring worries about the protective effect of surface penetrants for concrete that may degrade. Surface finishing before coating increases construction costs and duration. This study focuses on the impact of surface bugholes on chloride penetration of concrete coated with surface penetrants. The surfaces of specimens have various sizes of bugholes. Specimens were immersed in a sodium chloride solution of 3% for 100 days. The test results show that silane-based penetrants have an excellent water-repellent effect even on a concrete surface with bugholes. The chloride penetration depth increased with increasing surface bughole size when the concrete surface was uncoated or coated with a low-water-repellent surface penetrant. For concrete surface treated with high-water-repellent surface penetrants, the influence of surface bugholes on chloride penetration was negligible.